OC-044 Introduction of an inflammatory bowel disease smart phone 'app': a qualitative study. (22nd June 2015) - Watson, AJM; Patience, L; Pisano, U; Heaney, D
Abstract : Introduction: A smart phone application (app) for patients with inflammatory bowel Disease (IBD), was introduced in April 2013 for IBD patients. Patients were requested to record symptoms daily on the app which were then sent behind the NHS firewall and were then available, via a dashboard system. The aim of this study was to perform qualitative analysis of patient focus groups formed for the study. Method: Two focus groups were arranged after the app had been in use for three months. One of the focus groups was with participating clinicians in the unit, and one with a sample of participating patients. Both were conducted by an external qualitative researcher (DH). Interviews were recorded with participants' permission, coded and analysed in Nvivo using a framework approach. 40 patients were recruited, and of these a purposive sample of 10 consented to participate in the focus group. Results: A framework analysis of the recordings revealed distinct themes. Technical features of the app – Patients felt the app easy to use despite some teething issues around connectivity. There were issues depending on the type of phone the patient was using. All patients had experienced some issues, but accepted this at this stage because the app was being tested, Some patients reported that they liked the fact they were all collecting the same information. Patients expressed few, if any, concerns about the security of information being recorded. Use of the app – All patients reported using the app every day with only some minor exceptions. This was because the data they were collecting was of real importance to them. There was genuine enthusiasm and support for this innovation. Patients felt self monitoring had begun to transform subsequent clinical encounters. Patients felt reassured that their symptoms were monitored by a specialist Nurse. Features of success – The ability of patients to transmit data directly to the clinical team was seen as critical by patients. The integration of the application into the healthcare delivery is another key feature. Patients who had not collected structured information about themselves before, reported that they were better able to think about their disease. Conclusion: Whilst it is still too early to ascertain whether this innovation is sustained and becomes normalised into everyday practice, the results from this study suggest it will. The ability for patients to send data directly to clinicians was seen as a key attribute of this development. Patients who had had a clinic visit since using the app felt it had made a significant impact on the consultation. This app fitted into patients lives and was tailored to their needs, and was a successful first step in releasing the potential that technology provides for this patient group. Disclosure of interest: None Declared.